Efecto de un compuesto nitrogenado sobre los parámetros productivos y económicos en pollos broiler. - Salinas Salinas, Luis Abrahan (Machala : Universidad Técnica de Machala, 2024)
The present study was carried out at the “Santa Inés” Farm, located at the Faculty of Agricultural Sciences of the Technical University of Machala, in the province of El Oro, Ecuador, following the guidelines of the Good Poultry Practices (GAP) Guide. The objective of the research was to evaluate the effect of the inclusion of a nitrogen compound in the balanced diet of broilers on productive and economic parameters, with the purpose of determining its viability as a nutritional additive. The study was of the experimental type, using a completely randomized design with five treatments and four replicates for each one. Two hundred one-day-old mixed Cobb 500 broilers were used, distributed in experimental units of 10 birds each. The control treatment (T1) consisted of a conventional diet without the compound, while treatments T2, T3, T4 and T5 included the nitrogen compound at different levels of inclusion. Optimal management conditions were guaranteed, considering factors such as ventilation, temperature, feeding, hydration and vaccination. The parameters evaluated included live weight, feed consumption, feed conversion rate, mortality, productive efficiency factor (PEF), weight per square meter and production costs. For the statistical analysis, Statgraphics Centurión XV.I. software was used, applying a one-factor ANOVA and Tukey's HSD test (95%) for the comparison of means. According to the results obtained, the inclusion of the nitrogen compound did not generate statistically significant differences in production parameters or production costs compared to the control group. This suggests that its use does not represent a clear competitive advantage in terms of productive or economic efficiency. Consequently, it is recommended that further studies be carried out with larger flocks and that possible combinations with other nutritional additives be explored to optimize their effect on poultry production.
El presente estudio se llevó a cabo en la Granja “Santa Inés”, ubicada en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala, en la provincia de El Oro, Ecuador, siguiendo los lineamientos de la Guía de Buenas Prácticas Avícolas (BPA). El objetivo de la investigación fue de medias. De acuerdo con los resultados obtenidos, la inclusión del compuesto nitrogenado no generó diferencias estadísticamente significativas en los parámetros productivos ni en los costos de producción en comparación con el grupo control. Esto sugiere que su uso no representa una ventaja competitiva clara en términos de eficiencia productiva o económica. En consecuencia, se recomienda realizar estudios adicionales con lotes de mayor tamaño y explorar posibles combinaciones con otros aditivos nutricionales para optimizar su efecto en la producción avícola.
Keywords: COMPUESTO NITROGENADO; PRODUCCION AVICOLA; PARAMETROS PRODUCTIVOS; COSTOS DE PRODUCCION